(untitled) (Przegląd Religioznawczy – The Religious Studies Review, 2020)
What is meant by “philosophy after Auschwitz”? How do we categorize thinkers into this discipline? Such categorization poses no problem where Jewish or German philosophers and theologians are concerned. In Poland, this type of thinking is commonly considered as virtually absent. Prof. Józef Tischner observed: “Heidegger says: ‘Man in his being was focused on his own being.’ Sartre says: ‘Hell is other people.’ Levi-Strauss says: ‘Hell is ourselves.’ Another structuralist says: ‘The end of the human being.’ And we have Kolbe.” The observation sounds ambiguous. On the one hand, it indicates the superiority of action, or “practical philosophy,” over purely speculative thinking, and it brings out philosophers’ ethical responsibility for theories they formulate. On the other hand, it suggests that Auschwitz as an event and a symbol may not have been thought out thoroughly enough. In this article, I seek to answer the question why the event of Auschwitz has had a different impact on Jewish and German religious thought than on thought in Poland, I discuss the ways the event comes to the surface, and I give an outline of Polish religious thinking “after Auschwitz.”